2019
DOI: 10.21873/anticanres.13499
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Inhibition of Protein Kinase CK2 and Dihydrofolate Reductase Results in Synergistic Effect on Acute Lymphoblastic Leukemia Cells

Abstract: Background/Aim: Recently, we demonstrated the ability of inhibitors of protein kinase 2 (casein kinase II; CK2) to enhance the efficacy of 5-fluorouracil, a thymidylate synthase (TYMS)-directed drug for anticancer treatment. The present study aimed to investigate the antileukemic effect of simultaneous inhibition of dihydrofolate reductase (DHFR), another enzyme involved in the thymidylate biosynthesis cycle, and CK2 in CCRF-CEM acute lymphoblastic leukemia cells. Materials and Methods: The influence of combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Since it has been shown previously that the TBBi derivative [ 11 , 31 ], as well as 5-FU [ 32 ], can affect cell cycle progression of breast cancer cells, the influence of 5-FU in combination with either 14B or CX-4945 on cell cycle progression was tested after 48 and 72 h of treatment in MDA-MB-231 cells. The cell cycle distribution profiles after treatment with each compound used separately and in two different combinations were determined by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…Since it has been shown previously that the TBBi derivative [ 11 , 31 ], as well as 5-FU [ 32 ], can affect cell cycle progression of breast cancer cells, the influence of 5-FU in combination with either 14B or CX-4945 on cell cycle progression was tested after 48 and 72 h of treatment in MDA-MB-231 cells. The cell cycle distribution profiles after treatment with each compound used separately and in two different combinations were determined by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…In ALL cells, a combined treatment with methotrexate and CX-4945 synergistically inhibited cell proliferation, blocked cell cycle progression in the G2/M phase and promoted the activation of caspases 3/7 [40]. The anti-tumour activity of methotrexate is brought about by inhibition of dihydrofolate reductase (DHFR), as well as of other enzymes involved in nucleotide synthesis.…”
Section: Acute Lymphoblastic Leukaemiamentioning
confidence: 99%
“…In many previous in vitro studies, tumour cells displayed growth inhibition mediated by CK2 inhibition. Studies have also shown reduced clonogenic survival following radiation in vitro and enhanced antitumor effects in vivo in some tumour models, suggesting a strong and promising radiosensitization potential for CK2 inhibiting agents (7)(8)(9)14).…”
Section: Discussionmentioning
confidence: 99%